Metasploit penetration testing cookbook : over 70 recipes to master the most widely used penetration testing framework - Singh, Abhinav (Packt Pub., 2012)
"This is a Cookbook which follows a practical task-based style. There are plenty of code and commands used for illustration which make your learning curve easy and quick. This book targets both professional penetration testers as well as new users of Metasploit who wish to gain expertise over the framework. The book requires basic knowledge of scanning, exploitation, and Ruby language"--EBL.